2012
DOI: 10.1111/ics.12016
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of solar lentigines by in vivo reflectance confocal microscopy: a longitudinal approach

Abstract: Solar lentigines are benign hyperpigmented skin lesions. Despite their widespread distribution, knowledge on the mechanisms of development is largely unknown. A clinical study was designed in which solar lentigines were characterized using various non-invasive clinical techniques. A subset of solar lentigines was followed over a 5-year time period. One hundred and twenty-eight solar lentigines were evaluated using in vivo reflectance confocal microscopy (RCM) for the evaluation of the length and density of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
3
24
0
1
Order By: Relevance
“…They are most commonly found on the face, hands, forearms, chest, and shins, erupting after chronic UV exposure . In the confocal images, it is possible to observe a regular epidermal honeycomb pattern, the alignment pattern of hyperrefractive basal cells around a nonrefractive papillary dermis in the dermoepidermal junction (DEJ), an increased number of dermal papillae, and a deformation of their alignment pattern . We did not observe any characteristics of inflammatory lesions such as melanophages in postinflammatory hyperpigmentation …”
Section: Discussionmentioning
confidence: 64%
“…They are most commonly found on the face, hands, forearms, chest, and shins, erupting after chronic UV exposure . In the confocal images, it is possible to observe a regular epidermal honeycomb pattern, the alignment pattern of hyperrefractive basal cells around a nonrefractive papillary dermis in the dermoepidermal junction (DEJ), an increased number of dermal papillae, and a deformation of their alignment pattern . We did not observe any characteristics of inflammatory lesions such as melanophages in postinflammatory hyperpigmentation …”
Section: Discussionmentioning
confidence: 64%
“…Both skin problems are induced by oxidative stress to the skin and have some similarities in their pathophysiology. Poor keratinocyte differentiation and aberrations to the DEJ are characteristic to both . As a result, agents that improve epidermal differentiation or reduce the negative effects of UV irradiation on keratinocyte differentiation are likely to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…With time, they darken and increase in size. Pollefliet et al showed, by imaging the same lentigines with RCM over a period of 5 years, how their morphology worsens with time as papillae get denser and less circular . Several works have focused on analyzing the biological mechanisms responsible for lentigo development.…”
Section: Discussionmentioning
confidence: 99%